Analisis Manajemen Resiko Aplikasi Rene Kasir Di Restoran Oemah Djari Salatiga Menggunakan ISO 31000 - Jecson Rambi Jecson; Melkior Sitokdana (APTIKOM SUMSEL, 2022)
The Rene Cashier application is an information system that serves to make it easier for staff to overcome customer queues in printing order receipts, inputting data sold by restaurants and storing restaurant sales data and making it easier for staff to arrange orders and customer seats, the information contained in Rene Cashier has been adjusted to the applicable restaurant regulations. In implementing an information system there must be risks that hinder the process of the system, so here a risk analysis is needed that aims to prevent or minimize the risks that will occur. By using ISO 31000 at Oemah Djari Restaurant Salatiga, it is expected to minimize the possible risks that will occur around the Rene Cashier application. The results of the ISO 31000 risk analysis are documents of possible risks that will occur around the Rene Cashier application, classifying possible risks and their impacts. So, the results of this study can be useful for Oemah Djari Restaurant Salatiga to prevent or at least minimize the risks that may occur in the Rene Cashier application.